Ionic fluxes of charged particles at cathode region - V. B. Oparin; M. V. Sosnina; K. N. Vinogradov (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2007)
We analyze the disperse particles charging at cathode region by collisional and diffusive mechanisms. The dependence of charge quantity at nanoparticles on their sizes and characteristics of motion in the electrical field is defined. It is shown that there is the velocity distribution of directed motion of charged particles to the cathode surface at cathode region, and as a result the dynamic coagulation is originated and leads to the size evolution of nanoparticles.